The Culture of the Highland Valley of Mexico. I. Life Around the Popocatepetl, a Dangerous Volcano (to continue) - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2010)
I want to dedicate this article about life, science and culture of the inhabitants around Popocatepetl, a living volcano, Puebla, Mexico. In addition, I formulated student research projects during autumn season and gave these to the six groups of students (each group consisting of four to six students), who were working under my guidance. They studied the social, religious and economic conditions of the inhabitants residing around and the vicinity of Popo. During three years of my stay as Professor in Chemistry and Biology Department of Universidad de las Americas, Puebla, I observed daily activities of Popocatepetl and described this experience here!